2022
DOI: 10.3389/fgene.2022.931803
|View full text |Cite
|
Sign up to set email alerts
|

ADD1 Single Nucleotide Polymorphisms Are Associated With Essential Hypertension Among Han and Mongolian Population in Inner Mongolia Area

Abstract: Aldosterone synthase (CYP11B2) and α-adducing (ADD1) are candidate genes that play key roles during essential hypertension (EH) incidence. However, the association between their genetic mutations and the risk of EH is unclear. The present study investigated specific single nucleotide polymorphisms (SNPs) from CYP11B2 and ADD1, and their potential role as risk factors for EH based on 423 Mongolian and 410 Han people in Inner Mongolia province. In the allelic model, people with ADD1 rs2239728-A presented a 0.74-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…However, the homoplasmic form, late onset and incomplete penetrance of EH observed in these Chinese families carrying the tRNA Glu mutations suggested that the m.A14693G and m.A14696G mutations were involved in the development of EH but may be insufficient to produce a clinical phenotype; hence, other factors such as nuclear genes (ADD1; ALDH1A3), 49,50 environmental components (air pollution), epigenetic modification (histone modification, DNA methylation) 51,52 and personal lifestyle (smoking or high salt intake) may contribute to EH expression in these two families. 53,54 In particular, mito-nuclear communication played a putative role in the pathogenesis of cardiovascular disease.…”
mentioning
confidence: 96%
“…However, the homoplasmic form, late onset and incomplete penetrance of EH observed in these Chinese families carrying the tRNA Glu mutations suggested that the m.A14693G and m.A14696G mutations were involved in the development of EH but may be insufficient to produce a clinical phenotype; hence, other factors such as nuclear genes (ADD1; ALDH1A3), 49,50 environmental components (air pollution), epigenetic modification (histone modification, DNA methylation) 51,52 and personal lifestyle (smoking or high salt intake) may contribute to EH expression in these two families. 53,54 In particular, mito-nuclear communication played a putative role in the pathogenesis of cardiovascular disease.…”
mentioning
confidence: 96%